Pride & Equality: A Phenomenological Study on the Experiences of LGBTQIA+ Employees in Novaliches Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
LGBTQIA+ individuals are more likely to face discrimination because they are oftenencouraged to conform to society's conventional views of being male or female. In this study,the researchers aimed to explore the lived experiences of LGBTQIA+ employees regardinggender discrimination in the workplace, particularly in Novaliches, Quezon City.Most of the LGBTQIA+ employees encountered problems with gender discrimination, such asGender Stereotyping and Gender Bias. They had different views and attitudes toward genderdiscrimination. Some of them react to it negatively, but most of them respond to genderdiscrimination positively. Gender discrimination also had different impacts on the participants.Most of them are influenced positively, some negatively, and others unbothered by genderdiscrimination. They also utilized different coping mechanisms to deal with those problemsbrought about by gender discrimination in the workplace. They were affected differently, bothpositively and negatively. However, despite that, they are still willing to advise their fellowLGBTQIA+ individuals who also experienced gender discrimination at their workplace. Lastly,the participants mentioned the desires they wish to attain in society as members of theLGBTQIA+ community who experienced gender discrimination in many forums.The results showed that most LGBTQIA+ employees encountered problems with genderdiscrimination. They had different views and attitudes toward gender discrimination. Genderdiscrimination also had different impacts on the participants. They also utilized different copingmechanisms to deal with those problems brought about by gender discrimination in theworkplace. It is recommended that LGBTQIA+ employees should continue to strive andmaintain a positive mindset despite being discriminated against because of theirgender.Government/Employment Agencies should create or improve policies that benefitpeople, regardless of gender, to provide everyone with equal job opportunities.
Keywords: Psychology